Seismic performance evaluation of steel frames with pre-pressed spring self-centering braces. (November 2019) - Fan, Xiaowei; Xu, Longhe; Li, Zhongxian
Abstract: Pre-pressed spring self-centering energy dissipation (PS-SCED) braces with flag-shaped hysteretic responses are expected to undergo large deformation while re-centering to their origin, providing a self-centering capability for the structures. Three 4-, 8-, and 16-story braced frames with PS-SCED braces were analyzed to assess their seismic performances in comparison to conventional steel braced frames (CSBFs) and buckling restrained braced frames (BRBFs). Detailed analytical models of the PS-SCED braces were implemented and seven suites of ground motions with three different hazard levels were used to assess the structural performances with respect to interstory drifts, residual deformations, and peak floor accelerations during earthquakes. It was shown that the CSBFs underwent larger average responses than the BRBFs and the PS-SCED braced frames. The interstory drifts and peak floor acceleration responses of the frames with the BRBs were comparable and often better than those of the frames with the PS-SCED braces due to their high energy dissipation and simpler hysteretic cycles; the difference in the performance of these two braces tended to decrease with the increase in the seismic hazard level and the building height. The PS-SCED braces reduced the residual deformations more effectively than the BRBs and CSBs. Highlights: PS-SCED braced frames were analyzed to assess their seismic performances. Interstory drifts and peak accelerations of BRBFs are often better than PS-SCED braced frames. Performance difference between BRB and PS-SCED braced frame tends to decrease as hazard level increases. PS-SCED braces reduce residual deformations more effectively than BRBs and CSBs.